BLOCK CHAIN BASED SMART HEALTHCARE SYSTEMS IN 5G NETWORKS. - SUJIHELEN, L.; SENTHILSINGH, C.; LIVINGSTON, L. M. MERLIN; SASIKUMAR, B. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
The 5G networks are about to deploy it all over the world. This 5G technologies support by connecting the devices with rapid growth in network capacity, high QoS. Apart from this feature, 5G has more advantages in security, decentralization, transparency, data interoperability. The 5G network has millions of IoT devices are connected. With higher speeds these devices are enabled and worked with high speed. Blockchain is an important technology in the current trend. The Blockchain technology is used in more fields such as online payments, healthcare, smart contracts etc. Extending the technology of block chain to Internet of things (IoT) can have more features. The important issues in 5G technology is security because millions of IoT devices are connected and more confidential data is transferred. This data should be more secure using blockchain technology. This proposed system is to secure the data in smart healthcare systems using blockchain in 5G networks to prevent the data from forgery.